دور التسويق السياحي في تحسين الأداء التسويقي في المؤسسة الفندقية دراسة حالة فندق الغزالة الذهبية بالوادي - السعيد،هزلاوي; فارس،جابا لله; نصر الدين،بيكي; تامة، احمد الخطيب (university of eloued جامعة الوادي, 2024)
الملخص تحاول هذه الدراسة الإجابة عن السؤال الآتي: ما مدى قدرة التسويق السياحي في تحسين الأداء التسويقي في المؤسسة الفندقية الغزالة الذهبية وهدفت هذه الدراسة إلى معرفة دور التسويق السياحي في تحسين الأداء التسويقي في المؤسسة الفندقية الغزالة الذهبية،من خلال تحديد أبعاد المزيج التسويقي الخدمي وأبعاد مؤشرات الأداء التسويقي متمثلة في كل من الربحية، الحصة السوقية،رضا الزبون، وقد اعتمدنا في قياس تحليلنا على المنهج الوصفي، والإستعانة بالمنهج التحليلي إلى جانب توزيع الإستبيان على عينة من الموظفين، وقد توصلت هذه الدراسة إلى مجموعة من النتائج أهمها وجود أثر إيجابي لدور التسويق السياحي في تحسين الأداء التسويقي في المؤسسة الفندقية الغزالة الذهبية، على مستوى الربحية،الحصة السوقية، رضا الزبون.كما أوصت الدراسة، بالتركيز على التدريب والتكوين المستمر للموظفين من أجل الحصول على أداء جيد وفعال على المؤسسة الفندقية الغزالة الذهبية وعلى خدمات في مستوى تطلعات الزبائن. Abstract: This study attempts to answer the following question: To what extent is tourism marketing able to improve marketing performance in the Golden Ghazala Hotel Corporation This study aimed to know the role of tourism marketing in improving the marketing performance in the Golden Ghazala Hotel Corporation, by identifying the dimensions of the service marketing mix and the dimensions of marketing performance indicators, represented by profitability, market share, and customer satisfaction. We relied on measuring our analysis on the descriptive approach. Using the analytical approach in addition to distributing the questionnaire to a sample of employees, this study reached a set of results, the most important of which is the presence of a positive impact of the role of tourism marketing in improving the marketing performance in the Golden Ghazala Hotel Corporation, at the level of profitability, market share, and customer satisfaction. The study also recommended By focusing on continuous training and training for employees in order to obtain good and effective performance at the Golden Ghazala Hotel Corporation and provide services that meet the expectations of customers.
مذكرة ماستر علوم تجارية